ASSESSMENT OF EXTENT OF SKILLS POSSESSED BY SECRETARIES FOR EFFECTIVE ELECTRONIC RECORDS MANAGEMENT IN POLYTECHNICS IN NORTH-CENTRAL, NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The study was aimed at assessing the extent of skills possessed by secretaries foreffective electronic records management in Polytechnics in North-Central, Nigeria.Two research questions guided the study. Two null hypotheses were tested at 0.05level of significance. The population of the study comprised 366 secretaries in tenPolytechnics in North-Central, Nigeria. A structured questionnaire with 27 items wasdeveloped by the researcher and validated by two experts. The Cronbach Alphacoefficient measure of internal consistency was used to test the reliability of theinstrument. The result of the reliability test for sections of the questionnaire 0.97 and0.68. The results of the reliability test yielded a value of 0.83 for the entire items in thequestionnaire respectively. Mean and standard deviation were used to answer thethree research questions. The z- test and ANOVA were used to analysis data relatingto the hypotheses. The findings revealed that all the electronic records managementskill areas assessed were moderately possessed by the secretaries. This implies thatsecretaries in Polytechnics in North-Central, Nigeria do not optimally possess skillsfor electronic record management. The findings further showed that there weresignificant differences in the mean ratings of male and female secretaries regardingthe level to which they possess skills for effective electronic records management.Also, there was a significant difference in the mean ratings of secretaries with regardsto years of working experience on the extent of electronic records management skillspossessed for effective records management. Based on the findings, it wasrecommended among others that Secretaries in Polytechnics in North-Central,Nigeria should immediately be trained by employers, through hands on training, inservice training, workshops, seminars, and conferences on effective electronic recordsmanagement.
Keywords: Assessment, Electronic records and Secretary